Molecular epidemiology of foot-and-mouth disease virus type A in South America - Malirat, Viviana (2012)
A databank of 78 VP1 complete sequences of type A foot-and-mouth disease virus (FMDV) from South American isolates was constructed. Forty-nine samples corresponded to FMDV that circulated between the years 1999–2008, mainly in Venezuela, where most type A outbreaks have occurred lately and twenty-nine to strains historically relevant for the continent. The phylogenetic analysis showed that all South American FMDV belonged to the Euro-SA topotype. Sixteen subgenotypes could be identified, based on a 15% nucleotide divergence cut-off criterion: eight are extinguished, three were active until the year 2002 and the remaining five circulated in Venezuela during the years 2001–2007, illustrating the potential for FMDV diversification under appropriate selective pressure. The last emergencies reported in already-free areas of Colombia in 2004 and 2008 were closely related to isolates acting in Venzuela. Evidence of positive selection over codon 170, within the immunogenic site 4 of VP1 protein, was recorded. A codon deletion in amino acid position 142, within the G–H loop, was found in some isolates within subgenotypes 14, 15 and 16. Conversely amino acid deletion 197 was restricted to all isolates within a particular genetic cluster. The present work is the first comprehensive phylogenetic analysis of FMDV type A in South America, filling a gap of knowledge with respect to both, historical and acting viruses. The results provided evidence that supports the ecosystem dynamics in the region, and also served as an input to establish genetic links of emergencies in already-declared free areas, highlighting the need for strengthening control activities.